PENGARUH INDEPENDENSI, MOTIVASI KERJA DAN INSENTIF TERHADAP KINERJA PENILAI PUBLIK PADA KANTOR JASA PENILAI PUBLIK DI KOTA SEMARANG - Taufiq, Mochamad; Haqq, Miftahul (Universitas Diponegoro, 2023)
The aim of this research is to analyze the influence of independence, work motivation and incentives on the performance of public assessors. The population in this study were all public appraisers at the Public Appraisal Services Office in Semarang City, totaling 109 people, while the sample was taken from all members of the population using the census method. However, 102 people returned the questionnaire and could be analyzed. The data analysis method used is multiple regression. The results of the analysis show that hypothesis 1 (H1) that independence has a positive effect on appraiser performance is proven. The regression coefficient for the independence variable has a positive sign, so it can be interpreted that the higher the independence, the higher the performance of the public appraiser. Hypothesis 2 (H2) that work motivation has a positive effect on the appraiser's performance is proven. The regression coefficient for the work motivation variable has a positive sign, so it can be interpreted that the higher the work motivation, the higher the performance of the public assessor. Hypothesis 3 (H3) that incentives have a positive effect on appraiser performance is proven. The regression coefficient for the incentive variable has a positive sign, so it can be interpreted that the more satisfying the incentives the appraiser receives from the company, the higher the performance of the public appraiser